IOT Enabled Health MonitoringSystem for Infants - Mansi Swami, Koena Biswas, Ms. K. Meenakshi, Aditya Sharma, AbhyudayaPurwar (International Journal of Advanced Science and Technology, 2020)
Healthcare is one of the  prime  concerns  of Indian population and with Infant Mortality  Rate  at  33  infant deaths per thousand live  births  in  2017  there  is  a  need for multi-functional IOT  (Internet  Of  Things)  systems  to monitor the vitals of patients. Wepresent a system  that logs and analyzes real-time temperature, pulse and heartbeat data  to  predict  possible  health  conditions  of   an   infant. The system also aims at monitoring the air quality of the surroundings to ensure a non-toxic environment for theinfants. Our system consists of multiple sensors that map  the  real-time readings to the micro controller which then sends them via a Wi-Fi module to the cloud. This data is used to predict any extreme health conditions which results in fatalities among newly born infants. We have also incorporated a Machine Learning module which uses Image  Classification  for jaundice detection. Our focus in this research work is to predict common health conditions in infants like jaundice, pneumonia and high fever which are common causes of death ininfants.